Inside Back Cover: Nucleation and Growth of Amino Acid and Peptide Supramolecular Polymers through Liquid–Liquid Phase Separation (Angew. Chem. Int. Ed. 50/2019). Issue 50 (12th November 2019) - Yuan, Chengqian; Levin, Aviad; Chen, Wei; Xing, Ruirui; Zou, Qianli; Herling, Therese W.; Challa, Pavan Kumar; Knowles, Tuomas P. J.; Yan, Xuehai
Abstract : The separation of the liquid phase into solute‐rich and solute‐poor phases is an elementary step leading to the nucleation of supramolecular nanofibrils from amphiphilic amino acids and peptides. As X. Yan, T. P. J. Knowles et al. show in their Research Article on page 18116 ff., the solute‐rich liquid droplets with low enthalpy act as nucleation sites, significantly decrease the nucleation barrier towards solid phase, and eventually form thermodynamically more favorable nanofibrils.